Esophageal Dysmotility in Patients following Total Laryngectomy. (12th December 2017) - Zhang, Teng; Maclean, Julia; Szczesniak, Michal; Bertrand, Paul P.; Quon, Harry; Tsang, Raymond K.; Wu, Peter I.; Graham, Peter; Cook, Ian J.
Abstract : Objectives: Dysphagia is common in total laryngectomees, with some symptoms suggesting esophageal dysmotility. Tracheoesophageal (TE) phonation requires effective esophagopharyngeal air passage. Hence, esophageal dysmotility may affect deglutition or TE phonation. This study aimed to determine (1) the characteristics of esophageal dysmotility in laryngectomees, (2) whether clinical history is sensitive in detecting esophageal dysmotility, and (3) the relationship between esophageal dysmotility and TE prosthesis dysfunction. Study Design: Multidisciplinary cross‐sectional study. Setting: Tertiary academic hospital. Subjects and Methods: For 31 participants undergone total laryngectomy 1 to 12 years prior, clinical histories were taken by a gastroenterologist and a speech pathologist experienced in managing dysphagia. Esophageal high‐resolution manometry was performed and analyzed using Chicago Classification v3.0. Results: Interpretable manometric studies were obtained in 23 (1 normal manometry). Esophageal dysmotility patterns included achalasia, esophagogastric junction outflow obstruction, diffuse esophageal spasm, and other major (30%) and minor (50%) peristaltic disorders. The sensitivity of predicting any esophageal dysmotility was 28%, but it is noteworthy that patients with achalasia and diffuse esophageal spasm (DES) were predicted. Two of 4 participants with TE puncture leakage had poor esophageal clearance. Of 20 TE speakers, 12 had voice problems, no correlation between poor voice, and any dysmotility pattern. Conclusions: Peristaltic and lower esophageal sphincter dysfunction are common in laryngectomees. Clinical history, while not predictive of minor motor abnormalities, predicted correctly cases with treatable spastic motor disorders. Dysmotility was not associated with poor phonation, although TE puncture leakage might be linked to poor esophageal clearance. Esophageal dysmotility should be considered in the laryngectomees with persisting dysphagia or leaking TE puncture.